2020
DOI: 10.3389/fendo.2020.00591
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is a diabetic complication which affects retinal function and results in severe loss of vision and relevant retinal diseases. Retinal vascular dysfunction caused by multifactors, such as advanced glycosylation end products and receptors, pro-inflammatory cytokines and chemokines, proliferator-activated receptor-γ disruption, growth factors, oxidative stress, and microRNA. These factors promote retinal endothelial dysfunction, which results in the development of DR. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 209 publications
1
68
0
8
Order By: Relevance
“…[10] Endo-Pat is of great significance for screening of high-risk population and has gradually been set as a clinical function evaluation indicator of vascular aging. [11,12] Infrared thermal imaging technology Infrared thermography, based on the principle of remote temperature measurement, records the infrared radiation wavelength emitted by human skin (affected by skin vascular relaxation and contraction factors) to analyze the multiple information of body surface temperature, and displays it in the form of thermal map, so as to reflect the microcirculation, the blood circulation of the lesion site, etc. [13] The study found that infrared thermal imaging technology has unique value in screening large population, detecting vascular function of chronic diseases such as hypertension, diabetes, and theirs complications.…”
Section: Journal Of Translational Internal Medicine / Aopmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Endo-Pat is of great significance for screening of high-risk population and has gradually been set as a clinical function evaluation indicator of vascular aging. [11,12] Infrared thermal imaging technology Infrared thermography, based on the principle of remote temperature measurement, records the infrared radiation wavelength emitted by human skin (affected by skin vascular relaxation and contraction factors) to analyze the multiple information of body surface temperature, and displays it in the form of thermal map, so as to reflect the microcirculation, the blood circulation of the lesion site, etc. [13] The study found that infrared thermal imaging technology has unique value in screening large population, detecting vascular function of chronic diseases such as hypertension, diabetes, and theirs complications.…”
Section: Journal Of Translational Internal Medicine / Aopmentioning
confidence: 99%
“…[ 10 ] Endo-Pat is of great significance for screening of high-risk population and has gradually been set as a clinical function evaluation indicator of vascular aging. [ 11 , 12 ]…”
Section: Functional Evaluation Of Vascular Agingmentioning
confidence: 99%
“…The underlying molecular mechanisms associated with vascular dysfunction, especially endothelial dysfunction, in DR are multifactorial. Chronic inflammation, oxidative stress, leukostasis, dysregulated growth factors and cytokines, and disruption of peroxisome proliferator-activated receptor-γ are mainly involved [ 98 ]. Diabetic retinopathy is prevalent in around 35% of patients with diabetes.…”
Section: Ocular Neurodegenerative Diseasesmentioning
confidence: 99%
“…AGE binding to RAGE receptors upregulates cyclooxygenase-2 (COX), resulting in monocyte activation and vascular cell dysfunction [79], linked to oxidative stress and NF-κB activation [80,81]. Finally, AGEs have been shown to stimulate endothelial cell proliferation and angiogenesis by upregulation of VEGF and via the RhoA/Rhoassociated protein kinase pathway [82,83].…”
Section: Receptor For Advanced Glycation End Products (Rage)mentioning
confidence: 99%